Proximate Characteristics and Nutritional Value of White Anchovy Flour (Medico Legal Update, 2020)
Low fish consumption in some parts of Indonesia is caused by the high price of several types of fish. Itsinclude types of fish that have a low social value in the community so it is less desirable although theirvalue of nutrients is very good. Anchovy is actually the best source of calcium and protein. Calcium inwhite anchovy (Stolephorus sp) is very stable resistant and not easily soluble in water. White anchovies(Stolephorus sp) are excellent as a source of calcium and protein in children who are in their infancy,expectant mothers, nursing mothers and adult women to prevent osteoporosis. When the production volumeof white anchovy (Stolephorus sp) is increased, making fish flour is a preservation method, It will makethe benefits of anchovy can be maximised. White anchovy flour quality can be measured by proximatecharacteristics and nutritional quality. Proximate parameters in this study are determination of water content,ash content, peroxide numbers, acid numbers, and saponification numbers. Nutritional quality analysis suchas carbohydrates, protein, fat, calcium, iron, fiber, zinc, DHA, EPA and trans fat. The characteristics of theproximate are good and meet the quality standards of a food product from fresh anchovy (Stolephorus sp)such as fiber content, ash content, number of peroxide and trans fatty acids. The best nutritional quality offresh anchovy (Stolephorus sp) are the content of protein, calcium, iron ,zinc, DHA and EPA.